Early body composition, but not body mass, is associated with future accelerated decline in muscle quality. Issue 3 (14th February 2017) - Fabbri, Elisa; Chiles Shaffer, Nancy; Gonzalez‐Freire, Marta; Shardell, Michelle D.; Zoli, Marco; Studenski, Stephanie A.; Ferrucci, Luigi
Abstract: Background: Muscle quality (MQ) or strength‐to‐mass ratio declines with aging, but the rate of MQ change with aging is highly heterogeneous across individuals. The identification of risk factors for accelerated MQ decline may offer clues to identity the underpinning physiological mechanisms and indicate targets for prevention and treatment. Using data from the Baltimore Longitudinal Study of Aging, we tested whether measures of body mass and body composition are associated with differential rates of changes in MQ with aging. Methods: Participants included 511 men and women, aged 50 years or older, followed for an average of 4 years (range: 1–8). MQ was operationalized as ratio between knee‐extension isokinetic strength and CT‐thigh muscle cross‐sectional area. Predictors included body mass and body composition measures: weight (kg), body mass index (BMI, kg/m 2 ), dual‐energy x‐ray absorptiometry‐measured total body fat mass (TFM, kg) and lean mass (TLM, kg), and body fatness (TFM/weight). Covariates were baseline age, sex, race, and body height. Results: Muscle quality showed a significant linear decline over the time of the follow up (average rate of decline 0.02 Nm/cm 2 per year, P < .001). Independent of covariates, neither baseline body weight ( P = .756) nor BMI ( P = .777) was predictive of longitudinal rate of decline in MQ. Instead, higher TFM and lower TLM at baseline predicted steeper longitudinal decline in MQ ( P = .036 and P < .001, respectively). In particular, participants with both high TFM and low TLM at baseline experienced the most dramatic decline compared with those with low TFM and high TLM (about 3% per year vs. 0.5% per year, respectively). Participants in the higher tertile of baseline body fatness presented a significantly faster decline of MQ than the rest of the population ( P = .021). Similar results were observed when body mass, TFM, and TLM were modeled as time‐dependent predictors. Conclusions: Body composition, but not weight nor BMI, is associated with future MQ decline, suggesting that preventive strategies aimed at maintaining good MQ with aging should specifically target body composition features.